2018
DOI: 10.3389/fnhum.2018.00414
|View full text |Cite
|
Sign up to set email alerts
|

Preserved but Less Efficient Control of Response Interference After Unilateral Lesions of the Striatum

Abstract: Previous research on the neural basis of cognitive control processes has mainly focused on cortical areas, while the role of subcortical structures in cognitive control is less clear. Models of basal ganglia function as well as clinical studies in neurodegenerative diseases suggest that the striatum (putamen and caudate nucleus) modulates the inhibition of interfering responses and thereby contributes to an important aspect of cognitive control, namely response interference control. To further investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 87 publications
4
9
0
Order By: Relevance
“…In line with previous studies that used a similar version of the unimanual Simon task 45 , 72 , behavioral results indicated a significant asymmetrical Simon effect. Thus, the current unimanual Simon task successfully elicited a stimulus–response conflict, which was more pronounced in the contralateral hemifield (i.e., in the visual field contralateral to the responding hand).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In line with previous studies that used a similar version of the unimanual Simon task 45 , 72 , behavioral results indicated a significant asymmetrical Simon effect. Thus, the current unimanual Simon task successfully elicited a stimulus–response conflict, which was more pronounced in the contralateral hemifield (i.e., in the visual field contralateral to the responding hand).…”
Section: Discussionsupporting
confidence: 90%
“…Accordingly, the dorsal striatum (i.e., caudate nucleus and putamen) should be involved in the control of response interference by putatively mediating the selection of task-appropriate responses and/or the selective inhibition of interfering response alternatives. In line with this assumption, our previous study in stroke patients indicated less efficient selective inhibition to resolve response interference after unilateral lesions of the striatum when taking into account the temporal dynamics of the interference control processes across the RT distribution 45 . Hence, we here hypothesized that the individual efficiency of selective inhibition as indexed by the decrease of the Simon effect across the RT distribution 49 is associated with (increased) activation of the dorsal striatum.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations